Leaching of Polycyclic Aromatic Hydrocarbons from the Coal Tar in Sewage Wastewater, Acidic and Alkaline Mine Drainage - Jean Bedel Batchamen Mougnol (International Journal of Environmental Research and Public Health, 2022)
Polycyclic aromatic hydrocarbons (PAHs) have been a problem in the environment for an extended period. They are mostly derived from petroleum, coal tar and oil spills that travel and are immobilized in wastewater/water sources. Their presence in the environment causes a hazard to humans due to their toxicity and carcinogenic properties. In the study, coal tar was analyzed using Gas Chromatography–Mass Spectrometry (GC–MS) and a concentration of 787.97 mg/L of naphthalene, followed by 632.15 mg/L of phenanthrene were found to be in the highest concentrations in the various water sources such as sewage, alkaline and acid mine drainage. A design column was used to investigate the leaching process and assessments were conducted on 300 mL of the various water sources mentioned, with 5 g of coal tar added and with monitoring for 4 weeks. The influence of the physiochemical properties of the receiving water sources, such as sewage, and acid and alkaline mine drainage, on the release of PAHs from the coal tar was assessed. The acidic media was proven to have the highest release of PAHs, with a total concentration of 7.1 mg/L of released PAHs, followed by 1.2 mg/L for the sewage, and lastly, 0.32 mg/L for the alkaline mine drainage at room temperature.